The scientific clues of Jesus Christ : a novel - Austin Ward, Enrique Daniel; Jones, Wesley (Panamá : Editorial Universitaria Carlos Manuel Gasteazoro, 2019)
The author wants to imply that religion is a means to send a message of biological transformation, with a powerful impact on the course of evolution as we understand it, and that this potential change would be related to notions of the structuring and management of biological energy. The message of Jesus Christ would be a coded message, almost mathematical, that, like all of natures great secrets, like geometric relationships and the Genetic Code, require a special effort to be understood and harnessed, and that this aspect is critical for the future of humanity and its exceptional possibilities. --
After a night of meditation -- At the cafe -- Between relative and perfect -- At the park -- Exploring: the superstructure and the ultra-structure -- Vital innovations in the management of energy -- The scientific clues -- The objective -- A new sensitivity -- More scientific clues: food -- The secret of faith and the ultra-structure -- A new perspective on the matter of temptations and pleasure -- Suffering and it´s negentropic meaning -- Tying loose ends about the progress of the ultra-structure and humility in the thermodynamic advantage -- The emerging exit.
Incluye índice.
Keywords: NOVELA PANAMEÑA; AUTORES PANAMEÑOS